Aromatic biobased polymer latex from cardanol. (August 2017) - Ladmiral, Vincent; Jeannin, Renaud; Fernandes Lizarazu, Kepa; Lai-Kee-Him, Josephine; Bron, Patrick; Lacroix-Desmazes, Patrick; Caillol, Sylvain
Graphical abstract: Highlights: Methacrylated cardanol (CAMA) monomer synthesis. CAMA radical polymerization in water emulsion. Synthesis of stable aromatic biobased latex. Film formation and photo-crosslinking by UV thiol-ene. Abstract: We present for the first time the aqueous emulsion radical polymerization of cardanol derived methacrylic monomer (CAMA) in order to pave the way for the replacement of styrene. This monomer was synthesized in two-step routes by epoxidation of cardanol prior to methacrylation. Polymerization of CAMA was studied both in toluene solution and in aqueous emulsion. Radical aqueous emulsion homo- and co-polymerization of CAMA with methyl methacrylate (MMA) were performed with sodium dodecyl sulfate as surfactant. Stable latexes were obtained with particle size between 25 and 75 nm. CAMA and MMA conversions were monitored versus time. Influence of radical initiator was studied on gel content, showing transfer to monomer in the case of persulfate as initiator. Glass transition temperature of homoPoly(CAMA) was determined and is suitable for coating application. Photo-crosslinking was performed by thiol-ene chemistry and allowed yielding cross-linked biobased aromatic coatings.